Design and kinematics analysis of coordinated variable wheel-track walking mechanism. (13th August 2020) - Zang, Liguo; Yang, Shaoqing; Wu, Chongyou; Wang, Xingyu; Teng, Fei
Wheeled walking mechanism has the advantages of high mobility and low rolling resistance, but it is easy to sink and slip when working in soft and muddy terrain. Tracked walking mechanism has the advantages of high passability and stability, but it has the problems of difficult steering and slow walking speed. In order to make the walking mechanism possess a combination of passability, stability, and mobility, a coordinated variable wheel-track walking mechanism was designed. The coordinated variable triangle track can change the landing area through the deformation structure to improve the ability of the walking mechanism to adapt to different terrains. The kinematics equation of the wheel-track walking mechanism was established, and the front wheel steering angle equation during motion was derived. Based on RecurDyn software, the motion simulation of the walking mechanism was carried out under the conditions of straight walking and turning on the flat ground, climbing hillsides, and crossing ditches. The simulation results show that the coordinated variable wheel-track walking mechanism has the mobility of wheeled walking mechanism and the passability and stability of the tracked walking mechanism. The stability and climbing ability of the wheel-track walking mechanism was better when the coordinated variable triangle track in the stretch state, and the mobility and steering ability was better in the contraction state.